1883 Ind. Acts 1712 - (:unkn) unknown (My University, 1883)
Pointing or Aiming Firearms a Misdemeanor, chap. 87, § 6678: Prohibited anyone over the age of ten to purposefully point any pistol, gun revolver, or other firearm, loaded or unloaded at or toward any other person. Violators fined not less than five hundred dollars.
Keywords: BRANDISHING